Phenotypic and genotypic characterization of near-isogenic lines targeting a major 4BL QTL responsible for pre-harvest sprouting in wheat - Xingyi Wang; Hui Liu; Guannan Liu; Md Sultan Mia; Kadambot H. M. Siddique; Guijun Yan (BMC Plant Biology, 2019)
Abstract Background Resistance to pre-harvest sprouting (PHS) is one of the major objectives in wheat breeding programs. However, the complex quantitative nature of this trait presents challenges when breeding for PHS resistance. Characterization of PHS using near-isogenic lines (NILs) targeting major quantitative trait locus/loci (QTL/QTLs) can be an effective strategy for the identification of responsible genes and underlying mechanisms. Results In this study, multiple pairs of NILs were developed and confirmed for a major QTL located on the 4BL chromosome arm that contributes to PHS resistance in wheat, using a combined heterogeneous inbred family method and a fast generation cycling system. Phenotypic characterization of these confirmed NILs revealed significant differences in PHS resistance between the isolines, where the presence of the resistant allele increased the resistance to sprouting on spikes by 54.0–81.9% (average 70.8%) and reduced seed germination by 59.4–70.5% (average 66.2%). The 90 K SNP genotyping assay on the confirmed NIL pairs identified eight SNPs on 4BL, associated with five candidate genes; two of the candidate genes were related to seed dormancy. Agronomic traits in the NIL pairs were investigated; both plant height and grain number per spike were positively correlated with PHS susceptibility. Conclusions This study confirmed multiple pairs of NILs and identified SNPs between PHS isolines, which are valuable resources for further fine-mapping of this locus to clone the major genes for PHS resistance and investigate the possible functional regulation of these genes on important agronomic traits, such as plant height and grain number per spike.